Hot Shot Hockey - Jake Maddox (Stone Arch Books, 2023)
Robyn Ray is a young hockey player with lots of speed and one big problem$1 (Bshe can$1 (Bt seem to make a goal. Can her formerly famous hockey star grandpa help her build the skills she needs to score? And will her team come together when it matters most?s
Keywords: Sport Stories -- Sport Stories